Analysis of Online Medical Services Availability during Covid-19 Pandemic In Nepal - Maharjan, Ramesh Kumar; Koirala, Shirshak; Maharjan, Rashmisha; Sherchand, Jeevan B. (Tribhuvan University Journal, 2020)
After the first case of COVID-19 reported from Wuhan City in China, the WHO declared it as a ‘pandemic’ on 11th March 2020. The first case of COVID-19 was officially announced in Nepal on 24th January 2020. The lockdown of the entire nation was implemented by the government of Nepal from 24th March 2020 following the announcement of the second positive case of COVID-19. The aims of the study to find out the available online services understand and analyze them to implement in Nepal.There are 10 online medical services operating to facilitate medical services and 13 Covid-19 related mobile apps to use by common public and medical surveillance within Nepal. These are online mobile application and online services dedicated to make life easy during Covid – 19 Pandemic in Nepal. It is better to apply single or minimize duplication of similar work for Covid-19 Pandemic in Nepal by different concerned authorities.